The Influence of Implementing the Whole Language Approach Type of Journal Writing on Improving Reading-Writing Literacy of Class II Students of UPT SDN Paccinongang Unggulan - Asis, Annisa Hikmah Ramadhani; Nurhaedah, Nurhaedah; Pagarra, Hamzah (Program Studi PGSD FIP UNM, 2024)
This experimental study aims to determine: 1) the implementation level of the whole language learning approach through journal writing for grade II students at UPT SDN Paccinongan Unggulan, 2) the improvement in reading-writing literacy of these students, and 3) the effect of this approach on their literacy skills. The research uses a Quasi Experimental Design with a Nonequivalent Control Group design. The population consists of all grade II students at UPT SDN Paccinongan Unggulan, with a sample size of 72 selected through purposive sampling. The independent variable is the whole language learning approach through journal writing, and the dependent variable is the improvement in reading and writing literacy. Data was collected through observations and tests, and analyzed using descriptive and inferential techniques. Descriptive analysis showed the journal writing approach was very well implemented in the learning process. Literacy skills, based on posttest results, improved from low to high in the experimental class. Inferential statistical analysis indicated a significant effect of the journal writing approach on literacy improvement, with a sig value of 0.002 < 0.05. Consequently, the application of this approach in the experimental class was highly effective, as evidenced by the improved implementation of the learning process from